Inhibition of miR-652-3p Regulates Lipid Metabolism and Inflammatory Cytokine Secretion of Macrophages to Alleviate Atherosclerosis by Improving TP53 Expression - Haiyun Liu; Changpeng Zuo; Lijuan Cao; Naiquan Yang; Tingbo Jiang (Hindawi Limited, 2022)
Purpose. The aim was to elucidate the regulatory function of miR-652-3p on lipid metabolism and inflammatory cytokine secretion of macrophages in atherosclerosis. Methods. miR-652-3p level in atherosclerosis patients, ox-LDL-treated macrophages, and their controls were monitored by Q-PCR. After ox-LDL treatment and miR-652-3p mimic, si-TP53 and their controls transfection, ELISA, and Q-PCR assays were used to detect IL-1ß, IL-6, and TNF-α levels. oil red O staining was processed to verify cholesterol accumulation. CE/TC and lipid metabolism were also detected. The protein levels of ABCA1, ABCG1, PPARα, CRT1, ADRP, and ALBP were detected by western blot assay. Based on the TargetScan database, the TP53 3'UTR region had complementary bases with miR-652-3p, which was also verified by dual-luciferase reporter gene assay. Finally, the regulation of miR-652-3p and TP53 was confirmed by rescue assay in atherosclerosis. Results. miR-652-3p is highly expressed in atherosclerosis, miR-652-3p inhibitor decreased IL-1β, IL-6, and TNF-α expression after ox-LDL treatment. Knockdown of miR-652-3p reduces foam formation in ox-LDL-treated macrophages. miR-652-3p inhibitor ameliorates cholesterol accumulation and lipid metabolism disorder. miR-652-3p negatively regulated TP53 in atherosclerosis. Si-TP53 rescued the effect of miR-652 inhibitor in atherosclerosis. Conclusion. miR-652-3p regulates the lipid metabolism of macrophages to alleviate atherosclerosis by inhibiting TP53 expression. It might be a potential target for atherosclerosis treatment.